2017
DOI: 10.1159/000484903
|View full text |Cite
|
Sign up to set email alerts
|

Combination Cyclophosphamide/Glucocorticoids Provide Better Tolerability and Outcomes versus Glucocorticoids Alone in Patients with Sjogren’s Associated Chronic Interstitial Nephritis

Abstract: Background: Steroid therapy has become an effective option for patients with primary Sjogren’s syndrome with tubulointerstitial nephritis (TIN), while the use of cytotoxic agents is still debated. Our study aimed to compare the clinical outcomes of patients treated with cyclophosphamide (CTX) combined with glucocorticoids with those of patients treated with glucocorticoids alone. Methods: All patients with primary Sjogren’s syndrome with chronic TIN admitted to the Division of Nephrology, Ruijin Hospital, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…However, a prospective study of 60 patients followed for a mean of nearly 4 years found that corticosteroids did not influence the progressive decrease in salivary flow rates 53. No controlled studies are published in primary-2002 patients, and only retrospective studies have reported the use of GCs for systemic disease,54 with a high rate of GC-related adverse events, including increased appetite and weight gain,52 a two-fold higher frequency of diabetes mellitus55 56 and Cushing in up to 80% of patients 56…”
Section: Resultsmentioning
confidence: 99%
“…However, a prospective study of 60 patients followed for a mean of nearly 4 years found that corticosteroids did not influence the progressive decrease in salivary flow rates 53. No controlled studies are published in primary-2002 patients, and only retrospective studies have reported the use of GCs for systemic disease,54 with a high rate of GC-related adverse events, including increased appetite and weight gain,52 a two-fold higher frequency of diabetes mellitus55 56 and Cushing in up to 80% of patients 56…”
Section: Resultsmentioning
confidence: 99%
“…119 Tubular interstitial nephritis (TIN) is the most common histological feature in patients with pSS-associated renal disease. 121 In this context, renal biopsies demonstrate marked infiltration by B lymphocytes and plasma cells, 122 similar to that seen in salivary glands. Typically, TIN in pSS is associated with distal renal tubular acidosis (RTA), 118,119,[123][124][125] and may lead to electrolyte imbalance (acidosis, hypokalemia, hypophosphatemia) 122 and rarely periodic paralysis.…”
Section: Renal Involvementmentioning
confidence: 90%
“…115 Although randomized controlled trials (RCTs) are lacking, corticosteroids and/or immunosuppressive/cytotoxic agents have been used, with anecdotal responses to treat renal disease complicating SS. 121…”
Section: Renal Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 patients had stable eGFR in 5-year follow-up. Shen et al [ 12 ] divided 70 pSS patients with chronic TIN into the corticosteroids (≥15 mg/day) and CTX (0.6–0.8 g/month) combination group (n = 14) and corticosteroids (≥15 mg/day) alone group (n = 56). After 12-month follow-up, the group with combination treatment had better eGFR improvement (21.35 ± 19.63 vs 2.72 ± 19.11 mL/min/1.73m 2 , P = .006).…”
Section: Discussionmentioning
confidence: 99%